Effectiveness of Extracorporeal Shockwave Lithotripsy in Removing Small and Large Stones - Muhammad Adeel Mahesar, Javed Altaf, Waqar Ahmed Memon, Abdul Qayoom Ghanghro, Taimoor Jatoi, Adeel Haider Arain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To examined the efficacy of extracorporeal shockwave lithotripsy in the removal of small and large stones. Study Design: Observational prospective study. Place and Duration of Study: Department of Urology, Liaquat University of Medical and Health Sciences, Jamshoro from 1st January 2018 to 31st January 2019. Methodology: Two hundred patients, 139 males and 61 females, who underwent extracorporeal shockwave lithotripsy for stones were enrolled. The participants were separated into two groups based on stone size group A (stones measuring between 1.5 to 2.0 cm) and group B (stones measuring between 2.0 and 2.5 cm). Patients who were pediatric or had co-morbidities were excluded. The number of extracorporeal shockwave lithotripsy sessions and the number of beams per session were determined based on the clearance of the stones, if the radiology report indicated that the stones were completely cleared or if fragments smaller than 2 mm in diameter were present. Results: In group A, only 26 patients had partial clearance while in group B only 2 patients had partial clearance. The majority of the patients in both groups did not report any complications. The most common complaint was isolated haematuria, with 9 (4.5%) patients in the one session group, 16 (8%) in the two session group, and 5 (2.5%) in the three or more session group reporting this symptom Two patients in group A had hematoma along with haematuria, one patient in group A had massive haematuria that required transfusion, and one patient in each group reported having steintrasse with haematuria. In addition, one patient in group A had an isolated hematoma. Conclusion: Extracorporeal shockwave lithotripsy is effective and first-line treatment option for small renal stones. For ureteric stones, the location of stones should be taken into account, as this can have an effect on the stone-free rate and efficacy of extracorporeal shockwave lithotripsy. Keywords: Extracorporeal shockwave lithotripsy (ESWL), Stone removal, Ureteric Stones, Haematuria